Three Paths to Full Employment Growth - Cornwall, John (Quarterly Journal of Economics, 1963)
I. Introduction, 1. — II. Fiscal policy and the multipliers in a static world, 3. — III. The effect of alternative fiscal policies on growth, 6. — IV. The effect of alternative fiscal policies on the budget, 11. — V. Fiscal policy and the multipliers in a dynamic world, 12. — VI. The effect of productivity on growth and the budget, 16. — VII. A Simulation experiment, 18. — VIII. Conclusions, 21. — Appendix, 22.